Scoping Review of National Antimicrobial Stewardship Activities in Eight African Countries and Adaptable Recommendations - Nduta Kamere; Sandra Tafadzwa Garwe; Oluwatosin Olugbenga Akinwotu; Chloe Tuck; Eva M. Krockow; Sara Yadav; Agbaje Ganiyu Olawale; Ayobami Hassan Diyaolu; Derick Munkombwe; Eric Muringu; Eva Prosper Muro; Felix Kaminyoghe; et al. (Antibiotics, 2022)
Antimicrobial resistance (AMR) is a global health problem threatening safe, effective healthcare delivery in all countries and settings. The ability of microorganisms to become resistant to the effects of antimicrobials is an inevitable evolutionary process. The misuse and overuse of antimicrobial agents have increased the importance of a global focus on antimicrobial stewardship (AMS). This review provides insight into the current AMS landscape and identifies contemporary actors and initiatives related to AMS projects in eight African countries (Ghana, Kenya, Malawi, Nigeria, Sierra Leone, Tanzania, Uganda, and Zambia), which form a network of countries participating in the Commonwealth Partnerships for Antimicrobial Stewardship (CwPAMS) programme. We focus on common themes across the eight countries, including the current status of AMR, infection prevention and control, AMR implementation strategies, AMS, antimicrobial surveillance, antimicrobial use, antimicrobial consumption surveillance, a one health approach, digital health, pre-service and in-service AMR and AMS training, access to and supply of medicines, and the impact of COVID-19. Recommendations suitable for adaptation are presented, including the development of a national AMS strategy and incorporation of AMS in pharmacists’ and other healthcare professionals’ curricula for pre-service and in-service training.